Reading Proclus and the Book of causes : Western scholarly networks and debates - Calma, Dragos (Studies in Platonism, Neoplatonism, and the Platonic tradition,, 2019)
"Reading Proclus and the Book of Causes, published in three volumes, is a fresh, comprehensive understanding of Proclus' legacy in the Hellenic, Byzantine, Islamic, Latin and Hebrew traditions. The history of the Book of Causes, an Islamic adaptation of mainly Proclus' Elements of Theology and Plotinus' Enneads, is reconsidered on the basis of newly discovered manuscripts. This first volume enriches our understanding of the diverse reception of Proclus' Elements of Theology and of the Book of Causes in the Western tradition where universities and religious schools offered unparalleled conditions of diffusion. The volume sheds light on overlooked authors, texts, literary genres and libraries from all major European universities from the 12th to the 16th centuries"--